Physiologic Implications of Reactive Oxygen Species Production by Mitochondrial Complex I Reverse Electron Transport - John O. Onukwufor; Brandon J. Berry; Andrew P. Wojtovich (MDPI AG, 2019)
Mitochondrial reactive oxygen species (ROS) can be either detrimental or beneficial depending on the amount, duration, and location of their production. Mitochondrial complex I is a component of the electron transport chain and transfers electrons from NADH to ubiquinone. Complex I is also a source of ROS production. Under certain thermodynamic conditions, electron transfer can reverse direction and reduce oxygen at complex I to generate ROS. Conditions that favor this reverse electron transport (RET) include highly reduced ubiquinone pools, high mitochondrial membrane potential, and accumulated metabolic substrates. Historically, complex I RET was associated with pathological conditions, causing oxidative stress. However, recent evidence suggests that ROS generation by complex I RET contributes to signaling events in cells and organisms. Collectively, these studies demonstrate that the impact of complex I RET, either beneficial or detrimental, can be determined by the timing and quantity of ROS production. In this article we review the role of site-specific ROS production at complex I in the contexts of pathology and physiologic signaling.